3D game development cube-it : front-end web app development - Lee, Alyssa Jay Lin (2016)
Websites are used all over the world. It is one of the most common forms of interactive media that is usually used by companies and individuals to share information.These information can range from background of a company, to how an item can be purchased. A website is very important, especially in this technologically advanced world today. When a piece of information is required, people tend to look up the Internet to search for what they need. This means that a website is often the initial point of contact one will have with the company or individual behind the website. As such, the website will be creating the very first impression one will have towards the owner of the website. Leaving a positive and lasting impression is especially important when it comes to websites for startups, just like Cube-It – a joining device and system which can be used in many areas. As new products usually begin relatively unknown, building up a good reputation is extremely important so as to garner interest and create business opportunities. Hence, developing the Cube-It website required in-depth planning and thought process.